The Impact of Exercise Load and Intensity on the Performance of China U24 3x3 Women Teams - Feng, Zijun; Zheng, Lei; Jiang, Jiayin (International Journal of Social Sciences and Public Administration, 2024)
This study analyzed the exercise load and exercise intensity of the China U24 3x3 women team in multiple games, combined with the performance data of the players in the game, and explored the impact of these factors on exercise performance. The results showed that there was a significant positive correlation between load intensity and average heart rate, and high load intensity usually led to a higher average heart rate. In addition, performance data such as scoring and rebounding were also significantly correlated with load intensity and load volume. Players with higher scores often underwent higher load volume and load intensity in the game. This shows that in high-intensity games, players' physical fitness and performance are closely related, and reasonable monitoring and management of load intensity are crucial to improving player performance and reducing the risk of injury. The study also showed that there were significant differences in load volume and load intensity between the U24 Blue Team and the U24 Red Team in different games, further emphasizing the importance of load management in game strategy and physical training. This study provides empirical evidence for basketball teams to formulate scientific training plans and game strategies, and emphasizes the importance of exercise load and intensity management to improve the overall performance of the team and the individual performance of the players.